2007
DOI: 10.1111/j.1469-1809.2007.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the PARK10 Gene in Parkinson Disease

Abstract: SummaryTwo recent association mapping studies in Parkinson disease (PD) reported three candidate genes for the PARK10 locus: EIF2B3 as a modifier of age-at-onset of PD (min P= 0.0004) and HIVEP3 as a PD risk gene (P ≤ 0.006) (Oliveira et al. 2005); and LOC200008 (CDCP2) identified by the whole genome association (WGA) study of PD of Maraganore et al. (2005). However, evaluation of the on-line PD WGA results revealed two significant SNPs in HIVEP3 in the two datasets, Tier 1 and Tier 2, used by Maraganore et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…They include CDR1 , a cerebellar degeneration-related protein; LRCH4 , a leucine-rich repeat-containing neuronal protein; CACNB2 , a subunit of voltage-gated calcium channel and involved in neuronal functions; and FAM123A ( AMER2 ), a member of the gene family involved in neurogenesis (Comai, Boutet, Neirijnck, & Schedl, 2010). Other commonly and most significantly affected genes also encode for proteins critical in cellular functions such as histone ( HIST1H4E ), transcription regulations ( ZGPAT , ERF , and HIVEP3 ) (Li et al, 2007), and mitochrondrial poly(A) polymerase ( PAPD1 ). A subsequent pathway-targeted analysis of GABAergic genes also revealed common expression changes in the cocaine addicts and alcoholics from our study, such as the downregulation of GABBR1 , GABRG2 , and GPHN , a gene encoding the associated scaffolding protein gephyrin (Enoch et al, 2012).…”
Section: Substance-specific and Shared Gene Expression Changes In mentioning
confidence: 99%
“…They include CDR1 , a cerebellar degeneration-related protein; LRCH4 , a leucine-rich repeat-containing neuronal protein; CACNB2 , a subunit of voltage-gated calcium channel and involved in neuronal functions; and FAM123A ( AMER2 ), a member of the gene family involved in neurogenesis (Comai, Boutet, Neirijnck, & Schedl, 2010). Other commonly and most significantly affected genes also encode for proteins critical in cellular functions such as histone ( HIST1H4E ), transcription regulations ( ZGPAT , ERF , and HIVEP3 ) (Li et al, 2007), and mitochrondrial poly(A) polymerase ( PAPD1 ). A subsequent pathway-targeted analysis of GABAergic genes also revealed common expression changes in the cocaine addicts and alcoholics from our study, such as the downregulation of GABBR1 , GABRG2 , and GPHN , a gene encoding the associated scaffolding protein gephyrin (Enoch et al, 2012).…”
Section: Substance-specific and Shared Gene Expression Changes In mentioning
confidence: 99%
“…In a recent study by the same group, the association between HIVEP3 SNPs and PD was still present when genotyping an extended series that included the original samples. 6 We found no association between HIVEP3 SNPs and PD (Table 1), including the most significant SNP from Li et al, 6 rs1105414 (previously known as rs3856255). Hence, our data do not support a role for HIVEP3 in the etiology of PD.…”
Section: Discussionmentioning
confidence: 80%
“…By examining CDCP2 SNPs in an expanded PD family dataset (293 multiplex and 467 singleton families) and a discordant sib-pair dataset, Li et al found no significant association of CDCP2 with PD [21]. They noted that the results confirmed previous negative findings for CDCP2 as a candidate PARK10 gene [21]. CDCP2 may influence seizure outcomes in numerous ways.…”
Section: Discussionmentioning
confidence: 93%
“…Maraganore et al stated that the CDCP2 protein had inferred oxidoreductase activity and was potentially involved in cholesterol biosynthesis and electron transport and mapped the CDCP2 gene to chromosome 1p32 [20]. By examining CDCP2 SNPs in an expanded PD family dataset (293 multiplex and 467 singleton families) and a discordant sib-pair dataset, Li et al found no significant association of CDCP2 with PD [21]. They noted that the results confirmed previous negative findings for CDCP2 as a candidate PARK10 gene [21].…”
Section: Discussionmentioning
confidence: 99%